Construction of novel small-molecule probes for real-time visualization of proteolytic enzyme functions - Mu, Jing (2017)
Proteolytic activities have received considerable attention given their vital roles in protein activation and degradation, which have been considered as extremely important pharmaceutical targets in the development of drugs and inhibitors for the treatment of cancer, bacterial or virus infection, and neurological disorders. Therefore, developing sensitive and accurate platforms to evaluate protease activities is necessary and critical in both scientific and biomedical areas. Fluorescent imaging has been extensively used in direct and non-invasive protein visualization, facilitating the study of protein localization and protein-protein interactions in living cells and organisms. Commonly used strategies are based on genetically encoded fluorescent proteins or tags into the protein of interest (POI). However, such genetic manipulations and in vitro assays fail to reflect the dynamic protease activities in living systems. Moreover, genetic fusion of fluorescent protein and tag probing labeling methods possibly perturb protein functions and thus affect cell physiology. Therefore, novel and sensitive platforms capable of real-time monitoring proteolytic activities and functions, especially in the pathological states are highly desired. In this dissertation, by taking the advantages of Förster Resonance Energy Transfer (FRET)-based small-molecule probes in the simplicity, sensitivity and amplified signal generation, the author attempted to develop a series of novel probes to visualize proteases activities at specific sites or organelles. In detail, the author firstly presents a simple and convenient method to visualize cell-surface proteolytic activities in living cells and tissues. The developed probe could be specifically cleaved by the membrane-associated furin-like enzymes, thereby recovering the fluorescence signals on the membrane of furin-expressed cells (Chapter 2). Subsequently, the proteolytic activities were visualized in single cell and the more detailed physical processes were investigated in chapter 3. In order to improve the diagnostic precision and specificity at the tumor microenvironment, a series of stimuli-responsive probes for selectively imaging furin-like enzyme activities are constructed. By using the optimal property of constructed photocaged probe, membrane-localized and endosome-localized proteolytic activities in living cells are achieved respectively, which presented great potentials for dynamically monitoring the furin-mediated processing of pathogens, virus or toxins at different sorting compartment.